PEMBERDAYAAN EKONOMI KERAKYATAN: PEMBUATAN MINYAK KELAPA MURNI (VIRGIN COCONUT OIL) DAN BLONDO DI DUSUN KRAJAN DESA BALET BARU KECAMATAN SUKOWONO KABUPATEN JEMBER - Anita Fitriya; Achmad Muhlis; Hamim Thohari (LP2M Universitas Ibrahimy, 2020)
The aim of this operation is to improve the economy of the new community of ballet villages by using pure coconut fruit as a medium to become virgin coconut OIL and Blondo. The strategy employed is to use approach learning. And using the tool for interviewing, socializing and recording. (1) This determination results in virgin coconut oil being very healthy for the skin. (2) Blondo and pure coconut oil are ideal for continuous production, since they have a reasonably high economic value. The opportunity for profit is very positive. (3) The nationalist economic policy focussing on the production of virgin coconut oil (VCO / Virgin Coconut Oil) and blondo has a positive influence on job growth. (4) Can conserve local culture (local wisdom), that is to say, making traditional cooking oil which is an ancient practice so that it needs to be produced. Keyword: Economy of the People; Pure coconut oil